1994
DOI: 10.1093/geront/34.3.332
|View full text |Cite
|
Sign up to set email alerts
|

On the Distinction of Suicide Ideation Versus Attempt in Elderly Psychiatric Inpatients

Abstract: A study of selected elderly psychiatric inpatients admitted for depression suggests that suicidal ideation may initiate a process of smoldering when the patient, family, and professionals interact in such a way as to dampen apparent distress. Suicidal thoughts and mood may be masked by affective or cognitive constriction, camouflaged by anxiety and external agitation, and "tranquilized" by anti-anxiety agents. Depression may go undetected. Distinguishing factors between attempters and ideators are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
1
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 0 publications
0
49
1
1
Order By: Relevance
“…These findings contrast with rates for suicide in old age, where the male to female ratio is around 4-6 : 1 (McIntosh, 1992). The majority of attempters were not married (Pierce, 1987;Upadhyaya et al, 1989;Merrill and Owens, 1990;Frierson, 1991;Nieto et al, 1992;Lyness et al, 1992;Nowers, 1993;Draper, 1994b;Schmid et al, 1994), with at least 45% of those aged 65 years and over being widowed. The divorcedlseparated account for 4-13% of attempts and have been reported to have the highest population rates (Hawton and Fagg, 1990).…”
Section: Demographymentioning
confidence: 93%
See 4 more Smart Citations
“…These findings contrast with rates for suicide in old age, where the male to female ratio is around 4-6 : 1 (McIntosh, 1992). The majority of attempters were not married (Pierce, 1987;Upadhyaya et al, 1989;Merrill and Owens, 1990;Frierson, 1991;Nieto et al, 1992;Lyness et al, 1992;Nowers, 1993;Draper, 1994b;Schmid et al, 1994), with at least 45% of those aged 65 years and over being widowed. The divorcedlseparated account for 4-13% of attempts and have been reported to have the highest population rates (Hawton and Fagg, 1990).…”
Section: Demographymentioning
confidence: 93%
“…None included data from general practice, which is relevant as a recent Belgian study found that only 70% of attempted suicides across all ages who were seen by general practitioners were referred to hospital (Van Casteren et al, 1993). Other sample biases noted were the restriction to self-poisoning attempts (Merrill and Owens, 1990), the inclusion of only 'serious' attempts (Nieto et al, 1992), the exclusion of near fatal attempts (Schmid et al, 1994) and the limitation to those requiring psychiatric admission (Lyness et al, 1992;Rifai et al, 1993) or assessment (Upadhyaya et al, 1989;Draper, 1994b).…”
Section: Demographymentioning
confidence: 99%
See 3 more Smart Citations